PENINGKATAN PRODUKSI BAWANG MERAH (Allium cepa L) DENGAN BERBAGAI MIKROORGANISME LOKAL - Gamawati Adinurani, Praptiningsih; Rekyani Puspitawati, Indah; Lesya Kusuma, Ardhy (JURNAL AGRI-TEK, 2018)
A field experiment was undertaken to study the effect of different Microorganism Local (MOL) on the growth, biomass yield and fresh bulb yield of onion (Allium cepa L.).  Eight kind treatment of MOL that is without MOL (M0), bamboo shoot (M1), banana hump (M2), snail (M3), fruit (M4), vegetable (M5), bael fruit (M6), salted fish (M7) and fish (M8).  The experiment was laid out in a Randomized Complete Block Design replicated three times. Application of Microorganism Local exerted significant influence on the plant length, number of tillers, bulb fresh weight, total of fresh and dry weight biomass, but no significant difference on the diameter of bulb and number of a bulb. The biggest increase of onion plant length on M6 (51,10) % and the number of tillers in M8 (115,31) %.  The effect of MOL type was significantly different on the fresh bulb weight, and M8  gave the highest weight 54,40 g/clump. The effect of diameter and number of bulb on the fresh weight is indicated by multiple regression equation Y = -33.52 + 28, 63 X1 + 3.12 X2 with coefficient of determination R2 = 0.870. Total fresh weight and dry of  plant biomass at most on  M8 treatment were 85,08 g / clump and 12,50 g / clump which was not different with M3. Keywords: bulb, dry weight biomass, microorganism local, onion